Market research matters : - Duboff, Robert (John wiley & Sons, Inc., 2000)
Market Research Matters provides you with tools to better align your companys market research and business forecast efforts to the overall business strategy and operations. It polishes the traditional marketing research techniques and reveals new ones that can help any company avoid the pitfalls of focusing only on the present–and seize the opportunities that an uncertain future has to offer